2016
DOI: 10.18632/oncotarget.10258
|View full text |Cite
|
Sign up to set email alerts
|

Obesity does not promote tumorigenesis of localized patient-derived prostate cancer xenografts

Abstract: There are established epidemiological links between obesity and the severity of prostate cancer. We directly tested this relationship by assessing tumorigenicity of patient-derived xenografts (PDXs) of moderate-grade localized prostate cancer in lean and obese severe combined immunodeficiency (SCID) mice. Mice were rendered obese and insulin resistant by high-fat feeding for 6 weeks prior to transplantation, and PDXs were assessed 10 weeks thereafter. Histological analysis of PDX grafts showed no differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The relevance of these data for humans has yet to be studied. One possibility is to set up PDX mice engrafted with the human tumor (Lo et al, 2016). The limitation of such study depends on the level of cross-reactivity between mouse and human CCR5 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of these data for humans has yet to be studied. One possibility is to set up PDX mice engrafted with the human tumor (Lo et al, 2016). The limitation of such study depends on the level of cross-reactivity between mouse and human CCR5 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that periprostatic fat, regarded as metabolically active visceral fat, is a distinct parameter instead of a surrogate marker for general obesity. Previous studies showed conflicting results in the link between PPF and tumorigenesis of PCa [ 7 9 , 32 ]. Further studies about the role of PPF in prostate carcinogenesis will be required to elucidate their association.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown HFD induced tumor progression via adipose-secretory cytokines or chemokines in TRAMP mice and within a xenograft mouse model of the prostate cancer cell line LNCaP (12)(13)(14). However, in a xenograft model of patient-derived prostate tumor tissue using immunodeficient mice, HFD was reported not to induce tumor progression (15). These results suggest that HFD might accelerate tumor progression of prostate cancer via interactions with immune responses including various cytokines.…”
Section: Introductionmentioning
confidence: 94%